2012
DOI: 10.1111/1469-0691.12010
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases in the Arabian Peninsula and Egypt

Abstract: Infectious diseases are important causes of morbidity and mortality globally. Epidemiologically, differences in the patterns of infectious diseases and antimicrobial resistance exist across diverse geographical regions. In this review on infectious diseases in the Arabian Peninsula and Egypt, the epidemiology of tuberculosis, malaria and human immunodeficiency virus (HIV) infections will be addressed. The challenges of the hepatitis C epidemic in Egypt and the epidemiology of this infection across the region w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 116 publications
(125 reference statements)
0
41
0
Order By: Relevance
“…It is well known that travels to and from DENV-endemic areas are common, and imported cases from eastern Africa (Zanzibar) were reported in Yemen as early as the nineteenth century ( 11 , 12 ). Circulation of different DENV serotypes has also been reported in Saudi Arabia: DENV-3 emerged as the predominant serotype after 1997, and DENV-2 and DENV-1 serotypes had been associated with earlier outbreaks ( 13 ). …”
Section: Discussionmentioning
confidence: 94%
“…It is well known that travels to and from DENV-endemic areas are common, and imported cases from eastern Africa (Zanzibar) were reported in Yemen as early as the nineteenth century ( 11 , 12 ). Circulation of different DENV serotypes has also been reported in Saudi Arabia: DENV-3 emerged as the predominant serotype after 1997, and DENV-2 and DENV-1 serotypes had been associated with earlier outbreaks ( 13 ). …”
Section: Discussionmentioning
confidence: 94%
“…Although studies have shown an increasing trend of phenotypic resistance to various antibiotics in CA-MRSA isolates from Saudi Arabia, no vancomycin resistance has yet been reported [30]. However, there are few data on the distribution of resistance genes [8].…”
Section: Discussionmentioning
confidence: 99%
“…It was first isolated in Saudi Arabia and described as a unique viral agent of Arabian Peninsula [6, 34]. Significantly, AHFV shares a high similarity with Kyasanur Forest disease virus, which was isolated in India [35].…”
Section: Hemorrhagic Fever Viruses Circulating In Tihamahmentioning
confidence: 99%
“…The Hajj rituals require sacrifice of livestock (more than 10–15 million small ruminants annually), and their importation from other countries may contribute to the global spread of those pathogens [6, 11]. …”
Section: Diagnosis and Disease Control Challengesmentioning
confidence: 99%
See 1 more Smart Citation